Lynch Syndrome—Impact of the Type of Deficient Mismatch Repair Gene Mutation on Diagnosis, Clinical Presentation, Surveillance and Therapeutic Approaches - Tudor Razvan Grigorie; Gheorghe Potlog; Sorin Tiberiu Alexandrescu (Medicina)
In today’s world, with its continuing advancements in genetics, the identification of Lynch syndrome (LS) increasingly relies on sophisticated genetic testing techniques. Most guidelines recommend a tailored surveillance program, as well as personalized prophylactic and therapeutic approaches, according to the type of dMMR gene mutation. Carriers of path_MLH1 and path_MSH2 genes have a higher risk of developing colorectal cancer (CRC), despite intensive colonoscopic surveillance. Conversely, carriers of path_MSH6 and path_PMS2 genes have a lower risk of developing CRC, which may be due to their lower penetrance and later age of onset. Thus, carriers of path_MLH1 or path_MSH2 would theoretically derive greater benefits from total colectomy, compared to low-risk carriers (path_MSH6 and path_PMS2), in which colonoscopic surveillance might achieve an efficient prophylaxis. Furthermore, regarding the risk of endometrial/ovarian cancer development, there is a global agreement to offer both hysterectomy and bilateral salpingo-oophorectomy to path_MLH1, path_MSH2 and path_MSH6 carriers after the age of 40. In patients with CRC, preoperative knowledge of the diagnosis of LS is of tremendous importance, due to the high risk of metachronous CRC. However, this risk depends on the type of dMMR gene mutation. For carriers of the high-risk variants (MLH1, MSH2 and EPCAM) who have already developed colon cancer, it is strongly recommended a subtotal or total colectomy is performed, while partial colectomy followed by endoscopic surveillance is an appropriate management approach to treat colon cancer in carriers of the low-risk variants (MSH6 and PMS2). On the other hand, extended surgery for index rectal cancer (such as total proctocolectomy) is less effective than extended surgery for index colon cancer from the point of view of metachronous CRC risk reduction, and is associated with a decreased quality of life.